Discovery of [18F]ACI‐12589, a Novel and Promising PET‐Tracer for Alpha‐Synuclein. (20th December 2022) - Capotosti, Francesca; Vokali, Efthymia; Molette, Jerome; Ravache, Myriam; Delgado, Christophe; Kocher, Jacqueline; Pittet, Laure; Vallet, Coralie; Serra, Andreia; Piorkowska, Kasia; Dimitrakopoulos, Ioannis K; Luthi‐Carter, Ruth; et al.
Abstract: Background: Parkinson's disease (PD) and other synucleinopathies such as Multiple System Atrophy (MSA) involve a progressive accumulation of a‐synuclein (a‐syn) inclusions that correlates with disease stage and clinical manifestations. The development of a PET agent capable of imaging a‐syn inclusions would significantly aid in differential diagnosis, staging, and monitoring possible benefits of candidate therapeutic agents targeting a‐syn. Due to the generally lower pathologic burden of a‐syn inclusions relative to other brain proteinopathies, a reliable a‐syn PET tracer must display high binding affinity and selectivity for its intended target. Method: Using our proprietary Morphomer ® library of low‐molecular weight and conformation‐specific ligands, compounds with good affinity and target occupancy were identified. We then iteratively performed medicinal chemistry optimization cycles to further improve on‐target binding properties and selectivity based on radiobinding and classical and high‐resolution autoradiography results. Optimized compounds were then assessed further for off‐target activities and evaluated for their brain pharmacokinetic properties in non‐human primates (NHPs). The clinical candidate [18F]ACI‐12589 was subsequently advanced through preclinical assessment prior to evaluation in a clinically diverse set of synucleinopathy subjects and controls. Result: Promising chemical scaffolds with high‐affinity binding to pathological a‐syn in tissue homogenates and sections have been optimized. Particularly, ACI‐12589 demonstrated improved target occupancy on different synucleinopathy samples, including PD and MSA, with a binding pattern aligning closely with the distribution of pathological a‐syn. Moreover, ACI‐12589 demonstrated selectivity for a‐syn versus other potential amyloid pathologies including amyloid‐beta, Tau, and TDP‐43. In NHPs [ 18 F]ACI‐12589 revealed good brain uptake, homogenous distribution and fast washout. Initial results from the ongoing clinical trials confirm favorable pharmacokinetic parameters in patients, including rapid signal equilibration, potentially allowing short scan times. Moreover, initial clinical data in MSA patients indicate that [ 18 F]ACI‐12589 uptake occurs in brain areas affected by the disease process based on clinical manifestations. Conclusion: [ 18 F]ACI‐12589 displays preclinical and clinical characteristics deemed necessary to become a reliable PET radiotracer for the imaging of a‐syn inclusions. Interestingly, ex‐vivo data from different synucleinopathy tissues is in accordance with the promising clinical data in MSA that will be presented by R. Smith et al. at this conference.